2011
DOI: 10.1088/0957-4484/22/25/254003
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical metallization memories—fundamentals, applications, prospects

Abstract: This review focuses on electrochemical metallization memory cells (ECM), highlighting their advantages as the next generation memories. In a brief introduction, the basic switching mechanism of ECM cells is described and the historical development is sketched. In a second part, the full spectra of materials and material combinations used for memory device prototypes and for dedicated studies are presented. In a third part, the specific thermodynamics and kinetics of nanosized electrochemical cells are describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
557
1
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 786 publications
(576 citation statements)
references
References 85 publications
14
557
1
4
Order By: Relevance
“…It has been reported that compared to the central area of the Cu electrode, the margin of the Cu electrode is apt to be oxidized to Cu(OH) 2 in air. 45 Therefore, the bulges are likely dominated by Cu(OH) 2 which is difficult to be removed by adhesive tape compared to Cu. We can thus conclude that only a single complete Cu filament forms after the Electroforming operation for Cu/ZnS/Pt ECM cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that compared to the central area of the Cu electrode, the margin of the Cu electrode is apt to be oxidized to Cu(OH) 2 in air. 45 Therefore, the bulges are likely dominated by Cu(OH) 2 which is difficult to be removed by adhesive tape compared to Cu. We can thus conclude that only a single complete Cu filament forms after the Electroforming operation for Cu/ZnS/Pt ECM cells.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 The ECM cell consists of an insulator layer sandwiched between two electrodes, in which one is made from an electrochemically active electrode (AE) metal, such as Ag or Cu, and the other is a counter electrode (CE), such as Pt, Ir, W, or Ag. 3,4 Till now, a large number of ECM cells have been reported, employing various insulating materials such as chalcogenides, [5][6][7][8][9][10][11][12][13] oxides, [14][15][16][17][18][19][20][21][22][23][24] amorphous Si (Refs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Among them, ReRAM has been extensively studied because of its non-volatile memory characteristics owing to its excellent retention, endurance and high on/off current ratio. [4][5][6][7] Furthermore, ReRAM has a simple two-terminal structure, fast switching speed and low power consumption with excellent scalability. ReRAM cells have been integrated into cross-point arrays (4F 2 ) to obtain an area-efficient structure for non-volatile memory applications.…”
Section: Introductionmentioning
confidence: 99%
“…4. 2,7,16 The subsequent reformation and dissolution of the metal filament take place at the same location on the Pt electrode. This situation is quite similar to that observed for a gap-type atomic switch, in which a metal bridge is formed between the tip of a scanning tunneling microscope (STM) and a sample.…”
Section: Resultsmentioning
confidence: 99%
“…6 Because it is constructed by electrochemical deposition and dissolution of a metal on an inert electrode, this type of cell is also referred to as an electrochemical metallization (ECM) cell. 7 It has been demonstrated that the oxide-based atomic switches exhibit an effect analogous to the long-term potentiation of biological synapses, suggesting their potential for use in neural computing systems. 8 Among the various properties of a RRAM operation, switching speed is one of the most important.…”
Section: Introductionmentioning
confidence: 99%